2013
DOI: 10.5480/1536-5026-34.3.182
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Podcast Lectures on Nursing Students' Knowledge Retention and Application

Abstract: Nurse educators should be aware of this finding when seeking to employ podcast lectures in nursing education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…No study reported an improvement in pharmacological knowledge in nursing students [ 12 13 ], but one found improved knowledge related to lung assessment [ 14 ]. Most students' knowledge was evaluated by quizzes developed for the studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No study reported an improvement in pharmacological knowledge in nursing students [ 12 13 ], but one found improved knowledge related to lung assessment [ 14 ]. Most students' knowledge was evaluated by quizzes developed for the studies.…”
Section: Resultsmentioning
confidence: 99%
“…This may be attributed to concerns over medication errors in clinical practice. Using a pharmacology database through the mobile device did not increase the students' pharmacology knowledge and thus, did not seem to improve the contextual knowledge retention of students [ 12 13 ]. However, the improved efficacy of drug dosage calculations might be considered a facilitating factor for better clinical practice in the future [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…One strategy, mobile learning (m-learning) such as podcasts, is an effective and flexible educational format that is grounded in "pedagogically sound characteristics to ensure effective implementation and learning" in nursing education. [30] Intentional supplemental podcasting of genetics/genomic content could potentially enhance the retention and application of this content. However, development and production of the podcast itself is a time-consuming endeavor.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, traditional learning techniques consider the teacher as the center of scientific knowledge, limiting the amount of knowledge acquired and retained. Abate 7 conducted research to demonstrate the retention of knowledge among students subjected to mobile learning, with nursing students as the primary participants. The study confirmed that the podcast lecture group recorded higher scores than students who used traditional learning methods.…”
Section: Introductionmentioning
confidence: 99%